COMPOSITE AUTOGRAFTS IN THE RECONSTRUCTION OF NASAL BITE WOUNDS - Bokhonko, Roman; Kavka, Maria; Savchyn, Vasyl; Pater, Yaroslav (Eastern Ukrainian Medical Journal, 2026)
Relevance. Bite wounds of the nose, especially with cartilage defects, are a complex tactical problem of plastic surgery. The purpose of the study. To study the indications and method of using composite flaps in the reconstruction of nasal defects due to a dog bite. Materials and methods. From 2016 to 2023, 9 patients with nasal bite wounds were treated at the Yuri Lypa Lviv Regional Hospital for War Veterans and Repressed. The patients were aged 18–68 (average age – 35.8). Among the injured, 3 (33.3%) were women. In the first 12 hours after the injury, 7 (77.8%) patients were hospitalized, the remaining 2 (22.2%) – in 12–72 hours. According to the collected medical history, 7 patients were bitten by their own dog, and the rest were bitten by stray animals. The bites occurred during the animal's food intake, washing (6), and in the rest of the patients, there were no provoking factors. The sanitary and veterinary services notified to determine the need for observation of the animals on a regular basis. All the victims showed signs of psycho-emotional stress due to the animal's aggression, awareness of the complexity of treatment and its cosmetic outcome. Passive tetanus prophylaxis was administered to each victim. The treatment was started under sedation after removing the bandage – the wound condition was assessed for contamination and foreign bodies, the depth of the defect (skin, exposed cartilage, bone), and the wound edges (signs of necrosis, inflammation). The primary surgical treatment of the wound consisted of stopping the bleeding, washing with isotonic saline, cleaning the edges with soap and iodine solution, and sparingly excising non-viable tissue. In all cases, defects of the skin, soft tissues and cartilage of the nose were diagnosed, which determined the need for the use of composite skin and cartilage autografts for their reconstruction. Results of the study. Surgical interventions were performed under endotracheal anesthesia. In 5 (55.6%) patients, plastic surgery of the soft tissue wound of the nose was performed with local tissues and supplemented with a composite skin and cartilage flap from the auricle, in 4 (44.4%) – with a full-layer autograft taken from the auricle. All patients were prescribed antibiotic therapy for 7 days, effective against aerobic and anaerobic microorganisms. There were no postoperative complications. The long-term cosmetic result is satisfactory. Conclusion. Adherence to the treatment tactics and timely health encounter of patients with nasal bite wounds allows to obtain good functional and cosmetic results. A significant defect of not only the soft tissues but also the cartilaginous structures of the nose determines the need for the use of composite skin and cartilage autografts, for which the auricle is a convenient donor site. Careful surgical technique of plastic surgery in these cases allows to achieve 100% graft engraftment and the desired cosmetic result.